2013
DOI: 10.1007/s11427-012-4427-3
|View full text |Cite
|
Sign up to set email alerts
|

A consensus linkage map of common carp (Cyprinus carpio L.) to compare the distribution and variation of QTLs associated with growth traits

Abstract: The ability to detect and identify quantitative trait loci (QTLs) in a single population is often limited. Analyzing multiple populations in QTL analysis improves the power of detecting QTLs and provides a better understanding of their functional allelic variation and distribution. In this study, a consensus map of the common carp was constructed, based on four populations, to compare the distribution and variation of QTLs. The consensus map spans 2371.6 cM across the 42 linkage groups and comprises 257 micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Growth-related traits (e.g., body weight and length) constitute the main purpose of genetic breeding projects in aquaculture. Earlier studies on common carp have confirmed a heritable basis in these traits [ 37 ], and some QTLs affecting growth-related traits have been reported [ 32 35 , 38 , 39 ]. For example, Laghari et al [ 32 ] performed analysis looking for BW, TL, and condition factor (K) based on a backcross common carp family, they detected 12 QTLs associated with BW and TL on ten LGs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Growth-related traits (e.g., body weight and length) constitute the main purpose of genetic breeding projects in aquaculture. Earlier studies on common carp have confirmed a heritable basis in these traits [ 37 ], and some QTLs affecting growth-related traits have been reported [ 32 35 , 38 , 39 ]. For example, Laghari et al [ 32 ] performed analysis looking for BW, TL, and condition factor (K) based on a backcross common carp family, they detected 12 QTLs associated with BW and TL on ten LGs.…”
Section: Discussionmentioning
confidence: 96%
“…The study also revealed that both major and minor genes differ in their genetic performance. Therefore, we concluded that the major genes are undergoing change and remain unfixed in these families [ 35 ]. Further investigation is needed to identify shared and overlapping QTLs in either populations or families to understand quantitative genetic variation.…”
Section: Introductionmentioning
confidence: 99%
“…Other linkage mapping studies for carps have estimated map lengths of widely differing sizes. For example, common carp map sizes range from 1852 cM to 5506 cM (between 161 and 719 and markers were used in these studies generating between 42 and 64 linkage groups [13-16]). Many of these size estimates are likely to be inaccurate due to poor coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the economic importance of C. carpio for the global aquaculture industry, as well as its importance as a model species for ecology, physiology, and evolutionary studies, over the past decade, researchers have developed a variety of genetic and genomics tool and resources. A large number of genetic markers have been developed, including microsatellites [ 3 , 4 ], and single nucleotide polymorphisms (SNPs) [ 5 , 6 ]. A number of genetic linkage maps have been constructed based on these markers [ 7 - 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of genetic linkage maps have been constructed based on these markers [ 7 - 10 ]. The markers have also been used to identify quantitative trait loci (QTLs) associated with economically important traits including growth rate, body shape, and meat quality [ 4 , 11 , 12 ]. A large set of expressed sequence tags (ESTs) have been generated using traditional cloning and Sanger sequencing methods, or next-generation transcriptome sequencing, and a cDNA microarray has been designed and constructed [ 13 - 17 ].…”
Section: Introductionmentioning
confidence: 99%